Genome-wide association study for atopy and allergic rhinitis in a Singapore Chinese population. - Anand Kumar Andiappan; De Yun Wang; Ramani Anantharaman; Pallavi Nilkanth Parate; Bani Kaur Suri; Hui Qi Low; Yi Li; Wanting Zhao; Paola Castagnoli; Jianjun Liu; Fook Tim Chew (PLoS ONE)
Allergic rhinitis (AR) is an atopic disease which affects about 600 million people worldwide and results from a complex interplay between genetic and environmental factors. However genetic association studies on known candidate genes yielded variable results. The aim of this study is to identify the genetic variants that influence predisposition towards allergic rhinitis in an ethnic Chinese population in Singapore using a genome-wide association study (GWAS) approach. A total of 4461 ethnic Chinese volunteers were recruited in Singapore and classified according to their allergic disease status. The GWAS included a discovery stage comparing 515 atopic cases (including 456 AR cases) and 486 non-allergic non-rhinitis (NANR) controls. The top SNPs were then validated in a replication cohort consisting of a separate 2323 atopic cases (including 676 AR cases) and 511 NANR controls. Two SNPs showed consistent association in both discovery and replication phases; MRPL4 SNP rs8111930 on 19q13.2 (OR = 0.69, P(combined) = 4.46×10(-05)) and BCAP SNP rs505010 on chromosome 10q24.1 (OR = 0.64, P(combined) = 1.10×10(-04)). In addition, we also replicated multiple associations within known candidates regions such as HLA-DQ and NPSR1 locus in the discovery phase. Our study suggests that MRPL4 and BCAP, key components of the HIF-1α and PI3K/Akt signaling pathways respectively, are two novel candidate genes for atopy and allergic rhinitis. Further study on these molecules and their signaling pathways would help in understanding of the pathogenesis of allergic rhinitis and identification of targets for new therapeutic intervention.